Athlete Leadership Development Within Teams: Current Understanding and Future Directions - Cotterill, Stewart T.; Loughead, Todd M.; Fransen, Katrien (Frontiers in Psychology, 2022)
Leadership has been shown to be a fundamental factor influencing the performance of sport teams. Within these teams, leadership can be provided by coaches, formal athlete leaders, such as team captains, and other ‘informal’ athlete leaders. The role of the athlete leader in a team, either formal or informal, has been consistently reported over the last 10 years to have a significant impact upon a teams’ functioning and effectiveness, as well as teammates’ general health and mental well-being. As such, cultivating the provision of this leadership within a team has emerged as an important focus for managers, coaches, sport psychologists, and scholars alike. While the recognition of the importance of athlete leadership is well established, there has been a lag in the development of systematic approaches to enhance and develop the leadership skills and capabilities of the athletes within sport teams. As a result, this paper seeks to review contemporary examples and current understanding of approaches to athlete leadership development. The paper will also highlight future areas for research and applied practice development.